2001
DOI: 10.1097/00001756-200103260-00050
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of P-CREB and expression of c-Fos in cochlear nucleus and superior olive following electrical intracochlear stimulation

Abstract: Investigating activity-dependent plasticity in the auditory brain stem of the adult rat, we observed that electrical intracochlear stimulation led to a tonotopically localized modulation of the phosphorylation of the cAMP response element binding protein (CREB) and an equally localized expression of the immediate early gene product c-Fos in cochlear nucleus and superior olive. As P-CREB is thought to act as transcription factor on one promoter site of the c-fos gene, we compared immunolabeling for P-CREB and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Others reported distinctly different patterns of c-Fos expression upon EIS (Illing & Michler, 2001;Saint Marie et al, 1999A, 1999B;Saito et al, 1999;Zhang et al, 1998). In several studies involving electrical stimulation, tonotopic patterns of c-Fos expression were found (Saito et al, 1999;Nagase et al, 2000;Saito et al, 2000;Illing & Michler, 2001), but others did not report it (Nakamura et al, 2005). c-Fos has also been induced after neonatal auditory deprivation (Keilmann & Herdegen, 1995; and in kanamycin-deafened rats (Fujii et al, 1997;Nagase et al, 2003).…”
Section: Electrical Stimulation Of the Auditory Pathwaymentioning
confidence: 98%
See 4 more Smart Citations
“…Others reported distinctly different patterns of c-Fos expression upon EIS (Illing & Michler, 2001;Saint Marie et al, 1999A, 1999B;Saito et al, 1999;Zhang et al, 1998). In several studies involving electrical stimulation, tonotopic patterns of c-Fos expression were found (Saito et al, 1999;Nagase et al, 2000;Saito et al, 2000;Illing & Michler, 2001), but others did not report it (Nakamura et al, 2005). c-Fos has also been induced after neonatal auditory deprivation (Keilmann & Herdegen, 1995; and in kanamycin-deafened rats (Fujii et al, 1997;Nagase et al, 2003).…”
Section: Electrical Stimulation Of the Auditory Pathwaymentioning
confidence: 98%
“…CREB phosphorylation is modulated in cochlear nucleus and superior olivary complex as a consequence of electrical stimulation in the cochlea (Illing & Michler, 2001). Apart from CRE, the c-fos promoter contains a sis inducible element (SIE), a serum response element (SRE), and an activator protein-1 (AP-1)-like sequence (FAP) (Herdegen & Leah, 1998.).…”
Section: Regulation Of C-fosmentioning
confidence: 99%
See 3 more Smart Citations